Response of Some Vegetative Growth Features of Broad Bean Vicia Faba L. To Foliar Fertilization With Some Macro And Micro Nutrients: RANA .R.ARRAK HAMEED K. ABDUL-AMEER BASMA. A.ASSAL - Arrak, Rana R.; Abdul-Ameer, Hameed K.; Assal, Basma A. (Journal of Kerbala for Agricultural Sciences, 2017)
Field experiment carried out within 2013/2014 in Altahyria region (35 km north Babylon province) to study the effect of spraying different levels of foliar fertilizers on plant growth of Vicia Faba .L local variety, the study included two factors representing three levels of nitrogen and phosphate fertilizer (PHOSS+Super Green) was (0, 10, and 20 ml.L.-1 ) , and three levels of potassium fertilizer with micronutrients KTE was (0, 10, and 20 ml.L-1) and their interaction , the factorial experiment designed at RCBD with three replicates. The results summarized as follows: There are significant differences between the spray levels for both factors and their interaction , the high levels of both fertilizer decrease significantly the early flowering process and maturity, increase plant height , number of branches, number of leaves , leaf area and the percentage of shoot dry matter compared to treatment without spraying. The 20 ml.L-1 treatment of PHOSS+Super green fertilizer gave 88.2 day , 114.6 day , 70.60 cm , 7.01 branch , 108.6 leaf , 1063.66 cm2 , and 31.80% respectively . While 20 ml.L-1 treatment of KTE fertilizer gave 91.0 day , 113.8 day , 73.47 cm , 6.97 branch , 99.0 leaf , 955.27 cm2 , and 31.30% respectively